2019
DOI: 10.1684/epd.2019.1076
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of extra‐hypothalamic epilepsies presenting with gelastic seizures

Abstract: We provide an overview of the surgical outcome of extra‐hypothalamic epilepsies with gelastic seizures based on an original case report and a summary of the literature. Twenty‐two articles providing information on the outcome of resective surgery in 39 patients with extra‐hypothalamic gelastic seizures from the temporal (19 patients) or frontal lobe (20 patients) were selected. We add another case of temporal lobe gelastic seizures to the literature with a video demonstrating the mirthful component of this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Sarigecili et al [ 10 ] reported a case of GS caused by nongalenic pial arteriovenous fistula in the right temporal lobe and joyful laughter occurred as a result. Joswig et al [ 11 ] reported a case of GS originating from the left temporal cortex and middle temporal lobe, which stimulated the anterior superior temporal gyrus to cause a typical burst of laughter. Dericioglu et al [ 12 ] reported a case of GS due to right temporal cortical dysplasia and laughter attacks as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Sarigecili et al [ 10 ] reported a case of GS caused by nongalenic pial arteriovenous fistula in the right temporal lobe and joyful laughter occurred as a result. Joswig et al [ 11 ] reported a case of GS originating from the left temporal cortex and middle temporal lobe, which stimulated the anterior superior temporal gyrus to cause a typical burst of laughter. Dericioglu et al [ 12 ] reported a case of GS due to right temporal cortical dysplasia and laughter attacks as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that the anterior cingulate region contributes to the motor aspect of laughter, while the processing of joy is due to the basal temporal cortex [2] . There have been multiple case reports of GS with frontal pathology, however there have only been 19 patients previously reported with temporal onset gelastic seizures, and none of them reported seizures secondary to a ganglioglioma [4] . All reported temporal lobe tumors leading to GS were amenable to surgical resection [4] .…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple case reports of GS with frontal pathology, however there have only been 19 patients previously reported with temporal onset gelastic seizures, and none of them reported seizures secondary to a ganglioglioma [4] . All reported temporal lobe tumors leading to GS were amenable to surgical resection [4] . The only report of a response to medication treatment with vigabatin was a patient with HH [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In temporal lobe epilepsies, common manifestations are present in auras, which could include hallucinations or auditory distortions, vertigo, or visual hallucinations and psychic or experiential phenomena, such as déjà vu, jamais vu, or fear. Another example are the so‐called “gelastic crises,” uncontrollable stereotyped laughter (with or without a feeling of joy), 14 as well as behavioral alterations that include ictal speech and vocalizations, 15 or affective behaviors (laughter, crying, or fear). In frontal lobe epilepsies, hypermotor seizures were described as “withdrawal behavior” (walk or run).…”
Section: Introductionmentioning
confidence: 99%